A review of the process of knowledge transfer and use of evidence in reproductive and child health in Ghana - Gordon Abekah-Nkrumah; Sombié Issiaka; Lokossou Virgil; Johnson Ermel (BMC, 2018)
Abstract Background The paper carries out a situational analysis to examine the production, dissemination and utilisation of reproductive and child health-related evidence to inform policy formulation in Ghana's health sector. Methods The study used Wald's model of knowledge production, transfer and utilisation as a conceptual model to collect relevant data via interviews and administration of questionnaire to a network of persons who either previously or currently hold policy-relevant positions in Ghana's health sector. Additional data was also gathered through a scoping review of the knowledge transfer and research utilisation literature, existing reproductive and child health policies, protocols and guidelines and information available on the websites of relevant institutions in Ghana's health sector. Results The findings of the study suggest that the health sector in Ghana has major strengths (strong knowledge production capacity, a positive environment for the promotion of evidence-informed policy) and opportunities (access to major donors who have the resources to fund good quality research and access to both local and international networks for collaborative research). What remains a challenge, however, is the absence of a robust institutional-wide mechanism for collating research needs and communicating these to researchers, communicating research findings in forms that are friendlier to policy-makers and the inability to incorporate funding for research into the budget of the health sector. Conclusion The study concludes, admonishing the Ministry of Health and its agencies to leverage on the existing strengths and opportunities to address the identified challenges.